2009
DOI: 10.1029/2008jc004943
|View full text |Cite
|
Sign up to set email alerts
|

Southward recirculation of the East China Sea Kuroshio west of Okinawa Island

Abstract: [1] The surface current of the Kuroshio recirculation region in the East China Sea is investigated. The surface currents in the west of Okinawa Island observed by HF radars and the assimilation results of the Japan Coastal Ocean Predictability Experiment (JCOPE) are analyzed. It appeared that currents in the easternmost edge of the Kuroshio bifurcate southward and flow into the west of Okinawa Island from JCOPE data. The currents are called Kuroshio southward recirculation currents. The currents are controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This means that more complicated dynamics are responsible for the seasonal variability of the Kuroshio Current at the PN section. Hisaki and Imadu (2009) suggested that the counter current on the right side of Kuroshio was controlled by bottom topography and was sometimes enhanced due to variability of the local wind stress curl. These studies suggest that the seasonal variability of the Kuroshio Current at the PN Section is related to both North Pacific basin scale wind stress variability and local wind stress variability; however, other factors such as the cooling effect can also play important roles (Oey et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…This means that more complicated dynamics are responsible for the seasonal variability of the Kuroshio Current at the PN section. Hisaki and Imadu (2009) suggested that the counter current on the right side of Kuroshio was controlled by bottom topography and was sometimes enhanced due to variability of the local wind stress curl. These studies suggest that the seasonal variability of the Kuroshio Current at the PN Section is related to both North Pacific basin scale wind stress variability and local wind stress variability; however, other factors such as the cooling effect can also play important roles (Oey et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Although the RUC is largely responsible for poleward heat transport, its contribution to the maintenance of marine ecosystem in the Nansei Archipelago is not substantial because the RUC's main body is situated at ~600 m below the surface (Ichikawa et al, ) where larvae and spawn of marine fauna are rare. The third mechanism is due to the transverse advective effects associated with the Kuroshio Counter Current, which often develops between the archipelago and the Kuroshio (e.g., Hisaki & Imadu, ; Ichikawa & Beardsley, ; Qiu & Imasato, , and references therein). The KCC manifests as a quasi‐persistent southwestward current with pronounced appearance of mesoscale eddies, extracting water from the Kuroshio, and transporting it toward the west coast of the archipelago.…”
Section: Introductionmentioning
confidence: 99%
“…Examples abound on the U.S. Pacific coast (e.g., Barrick et al 1977;Paduan and Cook 1997;Lipphardt et al 2000;Nishimoto and Washburn 2002;Beckenbach and Washburn 2004;Kosro 2005;Roughan et al 2005;Kaplan et al 2009;Kim et al 2009), the U.S. Atlantic coast (e.g., Shay et al 2002Shay et al , 2008Graber et al 1996;Marmorino et al 1999;Haus et al 2000;Chant et al 2004;Kohut et al 2008;Roarty et al 2008;Dzwonkowski et al 2009;Parks et al 2009), the European coastal seas (e.g., Prandle and Ryder 1985;Gurgel et al 1999;Kovacevic et al 2004;Cosoli et al 2005;Abascal et al 2009;Gacic et al 2009;Molcard et al 2009;Sentchev et al 2009), and the Asian marginal seas (e.g., Takeoka et al 1995;Yang et al 2005;Ebuchi et al 2006;Yoshikawa et al 2007;Ichikawa et al 2008;Zhu et al 2008;Hisaki and Imadu 2009;Takahashi et al 2009). Applications are now found over much of the world's coastal oceans.…”
Section: Introductionmentioning
confidence: 99%